Review on graphene nanoribbon devices for logic applications. (February 2016) - Marmolejo-Tejada, Juan M.; Velasco-Medina, Jaime
Abstract: Graphene nanoribbon (GNR) devices are being extensively investigated as possible candidates for replacing silicon-channel devices in the next-generation integrated circuits and systems, due to their attractive physical properties for electronic applications. This requires to implement complete models to effectively predict the electronic transport behavior of the device, which should be modeled in circuit level simulators before reaching commercial production. Different methods for electronic transport simulations in nanoelectronic devices have been studied, comprising first-principle, empirical, semi-empirical and analytical. They can be used according to the complexity of the device, and the number of atoms and inter-atomic interactions that need to be considered. This work summarizes the methods and models used to characterize and simulate nanoelectronic devices. Additionally, we review the properties of GNRs, defect issues and the most recent approaches and manufacturing techniques that could be used to design GNR-based logic circuits.